Coating of betanin and carvone Co-loaded nanoliposomes with synthesized cationic inulin: A strategy for enhancing the stability and bioavailability. (30th March 2022) - Amjadi, Sajed; Almasi, Hadi; Hamishehkar, Hamed; Alizadeh Khaledabad, Mohammad; Lim, Loong-Tak
Highlights: Betanin (BET) and carvone (CAR) were successfully co-loaded in nanoliposomes (NLPs) The NLPs were successfully coated with the synthesized cationic inulin (CI) The coated NLPs had a spherical and core–shell structure. Coating of NLPs with CI provided in vitro sustained release profile for BET and CAR. The thermal, physical, and oxidative stability of NLPs were improved by coating. Abstract: Betanin (BET) and carvone (CAR) as antioxidant and antibacterial compounds were co-loaded in the coated nanoliposomes (NLPs) with cationic inulin to improve their stability and bioavailability. A cationic inulin was successfully synthesized and used for surface coating of the NLPs. The zeta potential, particle size, and PDI values of the coated NLPs were 21.70 ± 7.00 mV, 143.5 ± 15.2 nm, and 0.35 ± 0.03 respectively. The encapsulation efficiency values of the coated NLPs for BE and CAR were 86.1 ± 3.9 and 77.2 ± 5.2 %, respectively. Electron microscopy results showed that the coated NLPs had spherical and core–shell structures. The slowest sustained release profile in the simulated gastrointestinal condition was obtained for the coated NLPs. The physical and oxidative stability of NLPs, as well as the physical stability of loaded compounds were improved by surface coating. In conclusion, the developed nanocarrier is a suitable platform to use all benefits of BET and CAR in the food industry.